Urban Ecosystem Services II: Toward a Sustainable Future - Russo, Alessio; Cirella, Giuseppe T. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The school of thought surrounding the urban ecosystem has increasingly become in vogue among researchers worldwide. Since half of the world's population lives in cities, urban ecosystem services have become essential to human health and wellbeing. Rapid urban growth has forced sustainable urban developers to rethink important steps by updating and, to some degree, recreating the human-ecosystem service linkage.Assessing as well as estimating the losses of ecosystem services can denote the essential effects of urbanization and increasingly indicate where cities fall short. This second book on urban ecosystem services contains 11 thoroughly refereed contributions published within the Special Issue "Urban Ecosystem Services II: Toward a Sustainable Future". The book addresses topics such as cultural ecosystem services, green infrastructure, urban trees, urban green spaces, and more. The contributions highlight current knowledge, gaps, and future research with the focus on building a sustainable future.